Short Term Isocaloric Ketogenic Diet Modulates NLRP3 Inflammasome Via B-hydroxybutyrate and Fibroblast Growth Factor 21 - Kim, Eun Ran; Kim, So Ra; Cho, Wonhee; Lee, Sang-Guk; Kim, Soo Hyun; Kim, Jin Hee; Choi, Eunhye; Kim, Jeong-Ho; Yu, Je-Wook; Lee, Byung-Wan; Kang, Eun Seok; Cha, Bong-Soo; et al. (Frontiers in Immunology, 2022)
A ketogenic diet (KD) is known to have beneficial health effects. Various types of KD interventions have been applied to manage metabolic syndrome based on modification of diet parameters such as duration of intervention, macronutrient components, and total calories. Nevertheless, the beneficial health impact of isocaloric KD is largely unknown, especially in healthy subjects. The present study investigated the acute effects of a 3-day isocaloric KD. In this non-randomized intervention study, we recruited 15 healthy volunteers aged 24-38 years (7 men and 8 women) and placed them on an isocaloric KD restricting intake of carbohydrates but not energy (75% fat, 20% protein, 5% carbohydrate) for 3 days. Biochemical profiles and laboratory measurements were performed. Peripheral blood monocular cells were cultured, and measured cell stimulated cytokines. After short-term isocaloric KD, subjects lost body weight and serum free fatty acid levels were increased. These results accompanied elevated serum β-hydroxybutyrate (BHB) concentration and fibroblast growth factor 21 (FGF21) levels and improved insulin sensitivity. Regarding the direct effect of BHB on inflammasome activation, interleukin-1β (IL-1β) and tumor necrosis factor-α secretion in response to adenosine triphosphate or palmitate stimulation in human macrophages decreased significantly after isocaloric KD. In ex-vivo experiments with macrophages, both FGF21 and BHB further reduced IL-1β secretion compared to either BHB or FGF21 alone. The inhibitory effect of FGF21 on IL-1β secretion was blunted with bafilomycin treatment, which blocked autophagy flux. In conclusion, isocaloric KD for 3 days is a promising approach to improve metabolic and inflammatory status. Clinical Trial Registration clinicaltrials.gov (NCT02964572).